Recruit fitness and police academy performance: a prospective validation study - Korre, Maria; Loh, K.; Eshleman, Emily J.; Lessa, Fábio S.; Porto, Luiz Guilherme Grossi; Christophi, Costas A.; Kales, Stefanos N. (My University, 2019)
Background: Police academies need fit recruits to successfully engage in training activities. In a previous retrospective study, we documented that recruits with poor fitness at entry to the academy had significantly lower graduation rates, and we also suggested evidence-based entry-level fitness recommendations. Aims: To validate our findings in a prospective cohort of police recruits. Methods: Recruits entering Massachusetts municipal police academies during 2015-16 were followed prospectively until they dropped out, failed or successfully graduated their academy classes. Entry-level fitness was quantified at the start of each training class using: body composition, push-ups, sit-ups, sit-and-reach and 1.5-mile run time. The primary outcome of interest was the odds of failure (not successfully graduating from an academy). We used logistic regression to assess the probability of not graduating, based on entry-level fitness. Results: On average, successful graduates were leaner and possessed better overall entry-level fitness. After adjusting for age, gender and body mass index, several fitness measures were strongly associated with academy failure: fewer sit-ups completed (OR 9.6 (95% CI 3.5-26.3) (≤15 versus 41-60)); fewer push-ups completed (OR 6.7 (95% CI 2.5-17.5) (≤20 versus 41-60)); and slower run times (OR 18.4 (95% CI 6.8-50.2) (1.5 miles in > 15 min 20 s versus 10 min 37 s to 12 min 33 s)). The prospective study results supported previously suggested minimum entry-level fitness (95% graduation rate) and target (98% graduation rate) recommendations. Conclusions: Push-ups completed and 1.5-mile run time at police academy entry were successfully validated as predictors of successful academy graduation, while sit-ups were also a strong independent predictor in the prospective study.
Keywords: Aerobic capacity; Fitness; Occupational health; Police academy; Push-up; Recruits